2016
DOI: 10.1016/j.anaerobe.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smokeless tobacco products on human oral bacteria growth and viability

Abstract: To evaluate the toxicity of smokeless tobacco products (STPs) on oral bacteria, seven smokeless tobacco aqueous extracts (STAEs) from major brands of STPs and three tobacco-specific N-nitrosamines (TSNAs) were used in a growth and viability test against 38 oral bacterial species or subspecies. All seven STAEs showed concentration-dependent effects on the growth and viability of tested oral bacteria under anaerobic culture conditions, although there were strain-to-strain variations. In the presence of 1 mg/ml S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
2
20
0
1
Order By: Relevance
“…High sugar content in STPs enhanced the growth of Lactobacillus casei and led to dental caries [25]. Our previous study showed that extracts from STPs affected the in vitro growth of some species of oral bacteria [26]. Taken together, these results suggest that STP may disrupt the ecological balance of oral microbiota; however, the impact of STPs on diversity and abundance of oral microbiota has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High sugar content in STPs enhanced the growth of Lactobacillus casei and led to dental caries [25]. Our previous study showed that extracts from STPs affected the in vitro growth of some species of oral bacteria [26]. Taken together, these results suggest that STP may disrupt the ecological balance of oral microbiota; however, the impact of STPs on diversity and abundance of oral microbiota has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous in vitro study showed similar results. Extracts from STPs could stimulate the growth of some bacteria at low concentration and inhibit the growth of some bacteria at high concentration [26]. These dose dependent effects might be due to the components of STPs, which contain high sugar content (added as sweetener) [27] and toxic compounds as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 A study on seven smokeless tobacco aqueous extracts showed a concentrationdependent effects on the growth and viability of oral bacteria cultured under anaerobic conditions. 22 These effects may be a result of increase superoxide anion production, lipid peroxidation, DNA fragmentation and DNA ladders caused by the use of chewing tobaccos. 23 Our result showed concentration dependent cell viability for the tuibur and nicotine treatment groups while the untreated negative control group showed 100% viability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, the use of smokeless tobacco is also associated with a wide range of adverse health issues, including cardiovascular diseases, weight loss, increased blood urea, and creatinine levels which seem to cause serious degenerative alterations and lead to periportal fibrosis in liver and edematous and calcified changes in renal glomerulus [7]. Aqueous extracts of ST hinder growths of some oral flora, which affect their balance, causing oxidative stress via degradation of nicotine into hydroxynicotine and cotinine-N-oxide inside the bacterium [8,9]. Furthermore, disruption of sperm-head morphology, decreased total sperm count, increased oxidative stress, and high genotoxic and germ cell toxic effects have been seen in animals treated with tobacco [10].…”
Section: Introductionmentioning
confidence: 99%